2014
DOI: 10.15274/inr-2014-10035
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Preprocedural Antiplatelet Medication in Coil Embolization of Ruptured Cerebral Aneurysms at the Acute Stage

Abstract: Preoperative antiplatelet medication for aneurysm coil embolization during acute subarachnoid hemorrhage (SAH) is not common. However, recent advances in neurointerventional devices make antiplatelet medication necessary for SAH surgery. We tested the hypothesis that preprocedural antiplatelet therapy in the acute stage of SAH prevents complications due to ischemia or induced bleeding. We retrospectively reviewed 35 consecutive ruptured cerebral saccular aneurysms that underwent coil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Further detailed analysis of patients in the International Subarachnoid Aneurysm Trial (ISAT)26 found that standard antiplatelet therapy did not affect the outcome at discharge or at the 1 year follow-up in patients with SAH. Shimamura et al 27 found that preprocedural antiplatelet medication did not affect the outcome of 35 consecutive SAH patients. In addition, Kato et al 28 investigated the influence of previous antiplatelet usage before stroke on the outcome of SAH patients with age.…”
Section: Discussionmentioning
confidence: 98%
“…Further detailed analysis of patients in the International Subarachnoid Aneurysm Trial (ISAT)26 found that standard antiplatelet therapy did not affect the outcome at discharge or at the 1 year follow-up in patients with SAH. Shimamura et al 27 found that preprocedural antiplatelet medication did not affect the outcome of 35 consecutive SAH patients. In addition, Kato et al 28 investigated the influence of previous antiplatelet usage before stroke on the outcome of SAH patients with age.…”
Section: Discussionmentioning
confidence: 98%
“…The safety and efficacy of antiplatelet therapy in aSAH have been proven (30)(31)(32). Antiplatelet therapy can improve the functional outcome in patients and reduce their risk of DCI.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review showed that com- plications of stent-assisted coiling for ruptured aneurysms may be affected by the method of antiplatelet administration. 15 Dual-antiplatelet medication with aspirin and clopidogrel 12,16 and monoantiplatelet therapy 1,2,6 have all been proved to be feasible for perioperative use on acutely ruptured aneurysms, and there is little consensus regarding the appropriate timing and dosage for antiplatelet agent administration, so further studies are required to establish the guidelines for perioperative antiplatelet strategy on stentassisted coiling for acutely ruptured aneurysms. 2) There is a changing strategy of case selection of coiling with stent placement in ruptured aneurysms.…”
Section: Discussionmentioning
confidence: 99%